An Audit of the Egress System in Multi-Storey Annexes of Four Halls of Residence at Knust, Kumasi, Ghana (Journal of Science and Technology, 2016)
Fire safety construction and fire safety equipment installations are important systems required for occupant safety. A principal consideration in this case is the provision of an effective egress system that could be located at appropriate places to aid people to safety. The absence of these measures in multi-storey blocks leaves occupants at greater risk. This paper presents results of a study carried out in students’ Halls of Residence at the Kwame Nkrumah University of Science and Technology (KNUST) in Ghana. Past and current statistics show an average of 300% increase in population of the multi-storey blocks on KNUST campus without any consideration of the capacity in the egress system. Documentation of the egress system in the halls of Residence was done by use of measured drawings and photography. A comparative analysis of the existing dimensions and standard dimensions revealed the narrow width, unequal treads and risers of steps and other inaccuracies of stair components. The results of the egress analysis showed the bottlenecks and constrictions that will be created when occupants rush out in an emergency. These lapses can be eliminated when proper circulation is introduced to the existing components and the construction of a suitable fire escape stair to aid occupants to a place of ultimate safety.